(untitled) (Scientific journal of the Fergana State University, 2023)
In this article different kind of theories are analysed about geographical place of Andijan city, historical position of nine brooks mentioned in “Boburnoma” by Z.M. Bobur and their contemporary conditions, related to Andijansoy, saving and keeping its water clean.